Use of an Osteoplastic Flap for the Prevention of Mastoidectomy Retroauricular Defects - Bento, Ricardo Ferreira; Tsuji, Robinson Koji; Fonseca, Anna Carolina de Oliveira; Alves, Ricardo Dourado (International Archives of Otorhinolaryngology, 2017)
Introduction After mastoidectomy, patients usually complain of bone depressions in the retroauricular region in the surgical site, especially in procedures that require extensive cortical resections. This causes inconveniences such as difficulty wearing glasses, cleaning, and aesthetics complaints.Objective This study aims to describe a vascularized flap surgical technique that uses the mastoid cortical bone adhered to the periosteum, which is pedicled on the anterior portion and repositioned at the end of the surgery. This ensures the coverage of the mastoid cavity generated by surgery and prevents ear retraction into the cavity. This preliminary report describes the technique and intraoperative and immediate postoperative complications.Methods After retroauricular incision, periosteal exposure is performed. A U-shaped incision is required for the procedure and delimits a periosteum area appropriate to the size of the mastoidectomy. The cortical bone is opened using a 2.5 mm drill around the perimeter of the “U,” at a 3 mm depth. A chisel is introduced through the surface cells of the mastoid, and a hammer evolves into the anterior direction. The flap is lifted, leaving the periosteum adhered to it and forming a cap. The flap is anteriorly fixed to not hinder the surgery, and repositioned at the end. The periosteum is then sutured to the adjacent periosteum.Results The first 14 cases had no intraoperative complications and were firm and stable when digital pressure was applied during the intraoperative and immediate postoperative periods.Conclusion The osteoplastic flap pedicle is a safe and simple procedure, with good results in the immediate postoperative period.
Keywords: mastoid; ear deformities; acquired; otologic surgical procedures; vascularized bone flap; wound closure techniques